gdbOF: A Debugging Tool for OpenFOAM - Marquez Damian, Santiago (2012)
OpenFOAM® libraries are a great contribution to CFD community and a powerful way to create solvers and other tools. Nevertheless in this creative process a deep knowledge is needed concerning with classes structure, for value storage in geometric fields and also for matrices resulting from equation systems, becoming a hard task for debugging. To help in this process a new tool, called gdbOF, attachable to gdb (GNU debugger) is presented in this paper. It allows to analyze classes structure at debugging time. This application is implemented by gdb macros, these macros can access to code classes and also to their data in a transparent way, giving the requested information. This tool is tested for different application cases, such as the assemble and storage of matrices in a scalar advective–diffusive problem, non orthogonal correction methods in purely diffusive tests and multiphase solvers based on Volume of Fluid Method. In these tests several types of data are checked, such as: internal and boundary vector and scalar values from solution fields, fluxes in cell faces, boundary patches and boundary conditions. As additional features of this tool data dumping to file and a graphical monitoring of fields are presented. All these capabilities give to gdbOF a wide range of use not only in academic tests but also in real problems.